Structure and electrochemical properties of PMMA-silica hybrid coatings modified with cerium and lithium ions - Trentin, Andressa [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This work reports on a detailed investigation of the structural and electrochemical properties of poly(methyl methacrylate) (PMMA)-silica coatings. Raman spectroscopy and thermal analysis showed that the fine-tuning of the benzoyl peroxide (BPO) amount, as a critical synthesis parameter, improves the polymerization efficiency of methyl methacrylate (MMA), leading to a highly cross-linked hybrid structure. Electrochemical impedance spectroscopy (EIS) showed for coatings deposited on carbon steel (A1020) and Al alloy (AA7075) a quasi-ideal capacitive impedance response, maintaining the low frequency impedance modulus of up to 10 GΩ cm2 essentially unchanged during 19 months of immersion in 3.5% NaCl. Although high performance passive coatings have been developed, pitting can significantly affect their durability. Hence, active corrosion inhibition induced by lithium and cerium ions in PMMA-silica sol-gel coatings was investigated. The addition of lithium carbonate yielded coatings with improved connectivity of nanometric silica cross-link nodes and stronger adhesion to the aluminum substrate. EIS results showed that higher lithium concentrations result in an increased impedance modulus and induce the self-healing ability, extending significantly the service life of the coatings. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) suggest that the regeneration process occurs by means of lithium ions leaching from the adjacent coating towards the corrosion spot, which is restored by a protective layer of Li containing aluminum hydroxide species. Finally, coatings loaded with Ce(III) and Ce(IV) provided long term protection for aluminum alloy, however only Ce(IV) imparts active inhibition due to the passivation of cathodic sites by forming highly insoluble Ce oxides and hydroxides. Intermediate Ce(IV) concentrations proved to be more effective in improving the barrier property combined with active protection of intact and damaged coatings over immersion time. In brief, this study found a close relationship between optimized structure, anticorrosive effectiveness and self-healing activity induced by lithium and cerium ions in PMMA-silica coatings, highlighting their high potential of the material for the effective protection of metallic surface.

Este trabalho relata uma investigação detalhada das propriedades estruturais e eletroquímicas de revestimentos de polimetilmetacrilato (PMMA)-sílica. Espectroscopia Raman e análise térmica mostraram que o ajuste da quantidade de peróxido de benzoíla (BPO), como um parâmetro crítico de síntese, melhora a eficiência de polimerização do metilmetacrilato (MMA), levando a uma estrutura híbrida altamente reticulada. A espectroscopia de impedância eletroquímica (EIS) mostrou para revestimentos depositados sobre aço carbono (A1020) e liga de Al (AA7075) uma resposta de impedância capacitiva quase ideal, mantendo o módulo de impedância de baixa frequência de até 10 GΩ cm2 essencialmente inalterado durante 19 meses de imersão em NaCl 3,5%. Embora revestimentos passivos de alto desempenho tenham sido desenvolvidos, pites de corrosão podem afetar significativamente sua durabilidade. Assim, a inibição da corrosão ativa induzida por íons lítio e cério em revestimentos de sílica sol-gel de PMMA foi investigada. A adição de carbonato de lítio produziu revestimentos com melhor conectividade dos nós de sílica nanométricos e forte adesão ao substrato de alumínio. Os resultados de EIS mostraram que as concentrações de lítio mais altas resultam em um aumento no módulo de impedância e induzem a autorregeneração que aumenta significativamente sua vida útil dos revestimentos. Time-of-flight secondary ion mass spectrometry (ToFSIMS) e a espectroscopia de fotoelétrons excitados por raios-X (XPS) sugerem que o processo de regeneração ocorre por meio de íons lítio lixiviados do revestimento adjacente em direção ao pite de corrosão, que é restaurado por uma camada de espécies de hidróxidos de alumínio contendo Li. Finalmente, os revestimentos contendo Ce(III) e Ce(IV) forneceram proteção de longo prazo para a liga de alumínio, porém somente Ce(IV) confere inibição ativa devido à passivação de sítios catódicos pela formação de óxidos e hidróxidos de Ce altamente insolúveis. As concentrações intermediárias de Ce(IV) mostraram-se mais eficazes para melhorar a propriedade de barreira combinada à proteção ativa de revestimentos intactos e danificados durante o tempo de imersão. Em resumo, este estudo encontrou uma relação íntima entre estrutura otimizada, eficácia anticorrosiva e atividade de self-healing induzida por íons lítio e cério em revestimentos PMMA-sílica, demostrando o alto potencial do material para eficiente proteção de superfícies metálicas.
Estrutura e propriedades eletroquímicas de revestimentos híbridos PMMA-sílica modificados com íons cério e lítio
Keywords: Revestimentos orgânico-inorgânicos; Híbrido PMMA-sílica; Carbonato de lítio; Ce(IV); Ce(III); Self-healing